El modelo mexicano de formación dual en la inserción laboral de los jóvenes en México - Thalheim, Luise Angela (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
The Mexican Dual Training Model (MMFD) is a public policy that promises to be a solution for the dilemma that exists between the business sector, which is in constant search for qualified workers with professional experience, and the youth unemployment in Mexico. This investigation describes and defines the origin, design and implementation of this educational model and discusses the first results in view of the fulfillment of the goals to connect the schools with the business sector and to place young graduates successfully in the labor market. A factorial analysis of correspondence verifies the positive relationship between, on the one hand, the variables of the MMFD, which are the number of schools, students enrolled, companies and graduates, and the unemployment rate of 18 to 29 year olds with upper secondary and higher education. On the other hand, between the variables of the Mexican Dual Training Model and the number of employed persons in the states that implement the model since 2013. The results of these analyses confirm the positive relationship between the Mexican Dual Training Model and the labor insertion. It can be said that, the higher the implementation indicators of this educational policy are, the bigger is the impact on the growth of the number of employed persons in the states and the more decreases the unemployment rate in the country. These results are optimistic in relation to the first official data and the potential to achieve the goals for which the model was proposed.

El Modelo Mexicano de Formación Dual (MMFD) es una Política Pública del sector educativo que prometa ser una solución para el dilema entre el sector empresarial, que está en búsqueda de empleados calificados con experiencia laboral, y el desempleo de los jóvenes en México. Esta investigación describe y define el origen, el diseño, la implementación de este modelo educativo y discute los primeros resultados obtenidos hacia el cumplimiento con las metas de la vinculación entre escuela y sector empresarial, así como la inserción de los jóvenes egresados en el mercado laboral. La comprobación de esta relación positiva se hace a través de un análisis factorial de correspondencia entre, por un lado, los variables del MMFD, que son el número de planteles, inscritos, empresas y egresados, y la tasa de desocupación de los jóvenes de 18 a 29 años de edad con educación media superior y superior, y por otro lado entre los variables del MMFD y el número de ocupados en las entidades federativas que implementan el modelo desde el año 2013. Los resultados de este modelo confirman la relación positiva entre la inserción laboral y el Modelo Mexicano de Formación Dual. Se puede decir que, con mayor escalamiento de esta política educativa, mayor es la incidencia hacia el crecimiento del número de ocupados en las entidades federativas y el decrecimiento de la tasa de desocupación en el país. Estos resultados son optimistas en relación con los primeros datos oficiales y el potencial de alcanzar las metas propuestas en el modelo.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Políticas Públicas
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2018-0312; Empleo para jóvenes; Desempleo en jóvenes; Educación dual; Educación medio superior; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1063